2011
DOI: 10.1186/1471-2407-11-96
|View full text |Cite
|
Sign up to set email alerts
|

Coffee consumption and risk of cancers: a meta-analysis of cohort studies

Abstract: BackgroundCoffee consumption has been shown to be associated with cancer of various sites in epidemiological studies. However, there is no comprehensive overview of the substantial body of epidemiologic evidence.MethodsWe searched MEDLINE, EMBASE, Science Citation Index Expanded and bibliographies of retrieved articles. Prospective cohort studies were included if they reported relative risks (RRs) and corresponding 95% confidence intervals (CIs) of various cancers with respect to frequency of coffee intake. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
136
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(155 citation statements)
references
References 82 publications
11
136
0
8
Order By: Relevance
“…Despite case-control and cohort studies having reported inconclusive results about the relationship between coffee intake and CHD (10) , it is plausible that the inverse association between light to moderate coffee consumption and all-cause mortality may be partially attributed to the protection against certain kinds of cardiovascular and cerebrovascular diseases. The associations of moderate coffee consumption with the incidence and mortality of cancer varied by body sites and low to moderate coffee consumption was inversely related to total cancer incidence (38) . Whether there is a reverse causality between light to moderate coffee drinking and reduced all-cause mortality requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite case-control and cohort studies having reported inconclusive results about the relationship between coffee intake and CHD (10) , it is plausible that the inverse association between light to moderate coffee consumption and all-cause mortality may be partially attributed to the protection against certain kinds of cardiovascular and cerebrovascular diseases. The associations of moderate coffee consumption with the incidence and mortality of cancer varied by body sites and low to moderate coffee consumption was inversely related to total cancer incidence (38) . Whether there is a reverse causality between light to moderate coffee drinking and reduced all-cause mortality requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple epidemiological studies have demonstrated an inverse association between coffee consumption and risk of colorectal cancer (4)(5)(6). However, the molecular basis of this effect remains to be fully understood (7).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that daily drinking of 4-6 cups of regular black coffee, meaning up to 750 mL, is sufficient to prevent carcinogenesis and slow the progression of different types of cancer [33]. The current body of evidence recommends coffee consumption to be included into a healthy lifestyle [30].…”
Section: Chemoprevention In Lung Cancermentioning
confidence: 99%